1999
DOI: 10.1021/la990074s
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahydrophobic and Ultralyophobic Surfaces:  Some Comments and Examples

Abstract: The preparation of ultrahydrophobic and ultralyophobic surfaces using several techniques is described. Plasma polymerization of 2,2,3,3,4,4,4-heptafluorobutyl acrylate on poly(ethylene terephthalate) yields surfaces with water contact angles of θA/θR = 174°/173°. Argon plasma etching of polypropylene in the presence of poly(tetrafluoroethylene) renders surfaces with water contact angles as high as θA/θR = 172°/169°. Surfaces of compressed pellets of submicrometer, variable-diameter spherical particles of PTFE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
1,001
0
5

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 1,183 publications
(1,023 citation statements)
references
References 27 publications
17
1,001
0
5
Order By: Relevance
“…This perspective is a consolidation of views that we have presented in one 2008, 9 two 2006, 10,11 and two 1999 12,13 papers. This perspective could be gleaned from these manuscripts, but its formulation would be difficult.…”
Section: Overviewmentioning
confidence: 79%
“…This perspective is a consolidation of views that we have presented in one 2008, 9 two 2006, 10,11 and two 1999 12,13 papers. This perspective could be gleaned from these manuscripts, but its formulation would be difficult.…”
Section: Overviewmentioning
confidence: 79%
“…[3,4] These studies address the critical issue of inducing surface roughness, which is required for true ultrahydrophobic behavior. [5][6][7][8][9][10][11][12][13][14][15] Soeno et al [3] described a multilayered polyelectrolyte/silica nanoparticle system which was heated to sinter the particles and burn off the polymer, then treated with a fluorosilane to induce the required hydrophobicity. Zhai et al [4] reported the formation of a pH-sensitive multilayer which undergoes a porosity-inducing phase transition in acidic solutions.…”
mentioning
confidence: 99%
“…In a recent critical evaluation of the "superhydrophobic" or "ultrahydrophobic" surface literature, Chen et al provide numerous examples of systems that are poorly defined because they fail to clearly present contact angle hysteresis. [14] Even very recent work falls short in this respect. [27] Following the recommendation of Chen et al, [14] we reserve the term "ultrahydrophobic" for those surfaces exhibiting both large water contact angles and small hysteresis between q a and q r .…”
mentioning
confidence: 99%
See 2 more Smart Citations